Revisiting the Need for Critical Research in Undergraduate Colombian English Language Teaching - Carlo Granados-Beltrán (Asociación Colombiana de Profesores de Ingles, 2018)
This article shares a reflection based on the relations found between the partial findings of two on-going projects in a BA program in bilingual education. The first study is named Critical Interculturality in Initial Language Teacher Education Programs whose partial data were obtained through interviews with four expert professors of Licensure programs across Colombia. The second project is Estado del Arte de los Trabajos de Grado 2009 - 2016, which involved an inventory of the theses done by students as graduation requirements for the BA program. Based on these data, the article urges a re-assessment of criticality in research at the undergraduate level by problematizing the hegemonization of action research, the instrumentalization of language and research, and the subalternity for those being researched.